Analysis of Determining Production Cost by Comparing Full Costing Method with Activity-Based Costing Method at UD. Ria Boga - Deri Kurniadi; Boby Rachman; Riko Ervil (SEKOLAH TINGGI TEKNOLOGI INDUSTRI PADANG, 2024)
RIA BOGA is one of the UMKM or Home Industries from Ponorogo Regency, engaged in the food sector, particularly in producing bread and cakes. Some of the products from UD. RIA BOGA include Bakpia Telo Ungu and Bolu. In determining the cost of production, UD. RIA BOGA still employs a simple calculation method and does not consider all production cost elements in its cost calculations. Consequently, this leads to confusion in the financial system of the business. This research aims to determine the appropriate method for calculating the cost of production at UD. Ria Boga. The results of this study show that the calculation of the cost of production using the full costing method in 2022 for the Bolu product is Rp 6,460.00, and for Bakpia Telo Ungu is Rp 9,837.00. Meanwhile, in 2022, the cost for the Bolu product is Rp 6,837.00, and for Bakpia Telo Ungu is Rp 8,804.00. The calculation using the Activity Based Costing method in 2021 for the Bolu product resulted in a production cost of Rp 6,309.00, while for Bakpia Telo, it was Rp 12,751.00. In 2022, the Bolu product had a production cost of Rp 6,637.00, and Bakpia Telo Ungu was Rp 11,662.00. The Activity Based Costing calculation considers the expenditure of each overhead cost on the product according to the consumption of each product activity, resulting in more accurate results.